2008
DOI: 10.1002/cncr.23317
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic properties and prognostic implications of the ubiquitin ligase Skp2 in cancer

Abstract: The expression of Skp2, the ubiquitin ligase subunit that targets p27Kip1 for degradation, is commonly overexpressed in human cancers. p27Kip1 is a negative regulator of the cell cycle that plays an important role in tumor suppression. Loss of p27Kip1 secondary to enhanced ubiquitin‐mediated degradation results in uncontrolled proliferation and promotes tumor progression. In the present study the prognostic implications of Skp2 are reviewed and the mechanisms that regulate its expression in different human can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
0
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 86 publications
(110 reference statements)
1
157
0
17
Order By: Relevance
“…38 Indeed, increased levels of Skp2 proteins are often observed in many human cancers where Skp2 overexpression is usually inversely correlated with reduced p27 expression, and positively correlated with tumor malignancy and poor prognosis in terms of cancer treatment. 39,40 Mechanistic studies show that, in addition to gene amplification and mRNA accumulation, deregulated proteolysis is also involved in elevated Skp2 expression in human cancers. We and other groups have demonstrated that in normal cell cycle, Cdh1/APC targets Skp2 for degradation, thus preventing premature entry into S phase.…”
Section: Methodsmentioning
confidence: 99%
“…38 Indeed, increased levels of Skp2 proteins are often observed in many human cancers where Skp2 overexpression is usually inversely correlated with reduced p27 expression, and positively correlated with tumor malignancy and poor prognosis in terms of cancer treatment. 39,40 Mechanistic studies show that, in addition to gene amplification and mRNA accumulation, deregulated proteolysis is also involved in elevated Skp2 expression in human cancers. We and other groups have demonstrated that in normal cell cycle, Cdh1/APC targets Skp2 for degradation, thus preventing premature entry into S phase.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, the results of our study favors the contention of Dardick et al [23] and others [2] that although composed histologically of the same tumor cells types, high grade MEC may represent a separate entity. Previous studies on a variety of human cancer types associated increased skp-2 expression with high grade tumors and aggressiveness [14][15][16]. The histogenesis of MST is probably relevant to the prediction of behavior [7].…”
Section: Discussionmentioning
confidence: 99%
“…The protein that specifically binds and targets p27 for degradation is S-phase kinase associated protein-2 (skp-2), and may be the main rate-limiting regulator for p27 degradation [13]. Previous studies on a variety of human cancers showed that an altered p27/skp-2 ratio was associated with poorer differentiation, aggressive biological behavior and worse clinical outcome [14][15][16]. In the present study, we retrospectively analyzed p27/skp-2 expression on a series of MSTs and sought to evaluate its usefulness as an MST histogenetic marker with relevance to tumor grade.…”
Section: Introductionmentioning
confidence: 99%
“…It also targets many other cellular proteins for degradation, including cyclin-dependent kinase inhibitors p21, p27 and p57, TOB1 (transducer of Erbb2), RASSF1 (Ras association domain family 1) and FOXO1 (forkhead box-containing transcription factor 1) (Frescas and Pagano, 2008). Upregulation of Skp2 has been shown in several types of cancers and may be an attractive target for the development of novel cancer- intervention strategies (Masuda et al, 2002;Yang et al, 2002;Yokoi et al, 2004;Sonoda et al, 2006;Chiappetta et al, 2007;Hershko, 2008). In melanoma, Skp2 expression is significantly increased, which correlates with a poorer patient survival Woenckhaus et al, 2005).…”
Section: Discussionmentioning
confidence: 99%